Implementation of the Drill Method to Improve Volleyball Underhand Pass Learning Outcomes - Mayori, Elsa; Eriyanti, Wiwi; Ridam; Jefri; Rahmad; Sasriani; Rahayu, Hastuti (Indonesian Journal of Sport Management, 2024)
Background: Volleyball instruction in schools aims to develop students' basic technical skills, one of which is the underhand pass, a crucial foundation of the game. However, many students still struggle with effective underhand passes due to a lack of technical mastery and targeted practice. Therefore, effective learning methods are needed to improve skills learning outcomes. Purpose: This study aims to determine the implementation of the drill method to improve the learning outcomes of volleyball underhand passing. Methods: This study is a classroom action research conducted in two cycles. The subjects in this study were 31 students of class XI. The instrument used was a volleyball underhand passing performance test. The data analysis technique was carried out descriptively by calculating the percentage of student learning outcomes completion in each cycle. Results: Based on the results of the analysis, it shows that in cycle I the number of students who completed the learning was 16 people or 51.6%, and those who had not completed were 15 people or 48.3%. After being given treatment in cycle II, the number of students who completed the learning increased to 28 people or 90.3%, and those who had not completed it decreased to 3 people or 9.7%. The increase from cycle I to cycle II was 38.7%. Conclusion: Based on the research results, it can be concluded that the implementation of the drill method has proven effective in improving learning outcomes in volleyball underhand passing. Through repeated, directed, and gradual practice, students are able to improve basic techniques, increase accuracy, and strengthen motor coordination in underhand passing. Furthermore, the drill method also has a positive impact on student motivation and activeness during the learning process. Therefore, the implementation of the drill method can be used as an alternative effective learning strategy to improve basic volleyball technical skills, particularly underhand passing. Implications and Recommendation: The results of this study indicate that the implementation of the drill method has a positive effect on improving learning outcomes in volleyball underhand passing. Physical education teachers are advised to routinely implement the drill method in teaching basic volleyball techniques, particularly underhand passing. Training should be structured in stages with a variety of drill formats to prevent boredom and maintain student motivation. Schools are expected to provide adequate facilities and infrastructure to support effective training.